2015
DOI: 10.1007/s00590-015-1610-9
|View full text |Cite
|
Sign up to set email alerts
|

Is unicompartmental knee arthroplasty (UKA) superior to total knee arthroplasty (TKA)? A systematic review and meta-analysis of randomized controlled trial

Abstract: In short-term outcomes (5 years or less, with follow-up of 0-5 years), TKA had higher postoperative complications than UKA, but had lower revision rates. There was only one study that reported long-term survivorship (more than 5 years, with follow-up of 5-15 years). Further research that assesses long-term survivorship is necessary to better evaluate UKA and TKA in the treatment of unicompartmental knee osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(86 citation statements)
references
References 28 publications
3
69
1
7
Order By: Relevance
“…The current treatment options for knee arthroplasty are still controversial where both UKA and TKA are both utilized to treat OA and ON. No consistent results have been shown in previous literatures; however, the use of both UKA and TKA has been increasing worldwide [ 15 ]. To our knowledge, this is the first study to examine the national database of patients that have undergone either UKA or TKA from 2005 to 2013 in Taiwan.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The current treatment options for knee arthroplasty are still controversial where both UKA and TKA are both utilized to treat OA and ON. No consistent results have been shown in previous literatures; however, the use of both UKA and TKA has been increasing worldwide [ 15 ]. To our knowledge, this is the first study to examine the national database of patients that have undergone either UKA or TKA from 2005 to 2013 in Taiwan.…”
Section: Discussionmentioning
confidence: 71%
“…By 2025, the percentage of the Taiwan population that is over 65 years old is forecast to increase up by 20% [ 17 ]. Some surgeons still might regard UKA as a temporary procedure and recommend that patients over 60 years of age are still best treated with TKA [ 15 ]. Our research has shown that the age distribution of patients receiving UKA is younger than in TKA.…”
Section: Discussionmentioning
confidence: 99%
“…KardiovaskulĂ€re, gastrointestinale, pulmonale und neurologische Ereignisse sind die wichtigsten allgemeinen Komplikationen. Dabei ist fĂŒr den unikondylĂ€ren OberflĂ€chenersatz eine geringere Komplikationsrate publiziert [23,41]. Lediglich kardiale und neurologische Ereignisse waren in einer der Studien gegenĂŒber dem bikondylĂ€ren OberflĂ€chenersatz vermehrt [23].…”
Section: Komplikationenunclassified
“…According to the severity and level of impairment, strategies for knee OA-related interventions include surgical and non-surgical approaches [5]. Among the nonsurgical, with prominent clinical use, pharmacologic interventions, which presently present a vast amount of intra-articular treatment approaches with results superior to non-steroidal anti-inflammatory drugs [6,7].…”
Section: Introductionmentioning
confidence: 99%